Peningkatan Kreativitas Masyarakat melalui Usaha Produk Olahan Tanaman Palawija di Nagari Sungai Durian, Solok, Sumatera Barat - Yulmira Yanti; Munzir Busniah; Zulfadly Syarif; Intan Sari Pasaribu (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
This community service program were based on the abundance of secondary crops in the Nagari Sungai Durian. This is because the soil and climate conditions in Nagari Sungai Durian are not suitable for cultivation of rice, so that local people choose to do cultivation of secondary crops. The most widely cultivated secondary crops are corn and cassava. Corn and cassava are crops that contain high carbohydrates. However, the selling value of corn and cassava yields were low. In addition, the processing product of corn and cassava do not vary, reduce the purchasing power of consumers. Then it is necessary to create a variety of processing product of corn and casava that are creative and innovative. The purpose of this community service activity is to increase the creativity of Nagari sungai durian community in producing various processed crop products especially corn and cassava into processing products that have economic value. This community service was done by socialization and secondary crops (cassava and maize) processing demo and the marketing of the products. This service was got positive response from the target community which shown by the participants enthusiasm and the new business formed after the service in Nagari Sungai Durian. This activity also increase business opportunities for Nagari Sungai Durian community so that it can increase the income of the community. Outcomes obtained from this activity are: a) The creation of public understanding in the importance of entrepreneurship; b) Community skills in processing various food products; c) Creating business opportunities for the community; d) Food products; e) Increase in communities incomes.